If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + -1(6 + -1b) = 22 3b + (6 * -1 + -1b * -1) = 22 3b + (-6 + 1b) = 22 Reorder the terms: -6 + 3b + 1b = 22 Combine like terms: 3b + 1b = 4b -6 + 4b = 22 Solving -6 + 4b = 22 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 4b = 22 + 6 Combine like terms: -6 + 6 = 0 0 + 4b = 22 + 6 4b = 22 + 6 Combine like terms: 22 + 6 = 28 4b = 28 Divide each side by '4'. b = 7 Simplifying b = 7
| x+3x=50000 | | 2r=72 | | 2(x+4)=4+4x | | Z^2-2z-24=0 | | 38(24-3.5x)=16(3x-10)+76.5 | | u^2+u-52=0 | | 3(x+2)=-2(x+4) | | -4(e+6)=-12 | | 4x+3=1x | | .65l+70=l | | 12x-5=24x+3 | | -4.65+0.19x=14.92 | | 20x-3+5x=22 | | 7y-5=9y+25 | | 0.12(y-6)+0.18y=0.04y-0.05(30) | | k-12=34 | | 4x^2+39x+56=0 | | -14=7(s-7) | | 15=(3h-1) | | 2-7[9-(6y-6)]= | | -4.65+0.19x=23.85 | | 7.4p-9.2p=-2.6+5.3 | | 5x^2-9x-80=0 | | -4+5x=-4x-4 | | Y-12=24 | | 7=4(5-2x)+3y | | 3(h-4)=-.5(24-6h) | | 7(3x-2)+18x+7=12x+7 | | (4n+17)+(n-2)=180 | | 9+t=14 | | (x+4)(x+4)+6=87 | | x+2=2x+15 |